Molybdenum and Tungsten Contamination in MOS Capacitors. (1st January 2016) - Polignano, M. L.; Galbiati, A.; Grasso, S.; Magni, D.; Mica, I.
Abstract : In this paper, the impact of molybdenum and tungsten contamination on the properties of MOS capacitors is analyzed, with the aim to investigate whether measurements of MOS capacitors can be used to detect this sort of contaminants. Surface Photovoltage (SPV) measurements of carrier diffusion length and of the oxide charge (obtained from high injection SPV) are compared to the results of MOS capacitor measurements. In agreement with previous DLTS data, both SPV and generation lifetime data show that molybdenum remains in the solid solution in silicon in the studied dose range. As a consequence, molybdenum contamination has limited impact on the interface state density at the oxide-silicon interface. Vice versa, tungsten was shown to deactivate starting from rather low doses (10 11 cm −2 ). Tungsten deactivation is associated with the formation of new peaks in interface state density spectra. However, no tungsten segregation at the oxide-silicon interface could be detected by ToF-SIMS measurements. We suggest that in MOS capacitors tungsten deactivation is associated with segregation in the oxide layer. SPV has limited sensitivity to these impurities. Generation lifetime is a good monitor of tungsten contamination, whereas for molybdenum DLTS is the most sensitive contamination monitor.